2015
DOI: 10.1136/bcr-2014-209157
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pedicled nasoseptal flap repair of spontaneous sphenoid sinus cerebrospinal fluid leaks

Abstract: SUMMARYSpontaneous cerebrospinal fluid (CSF) leaks in the sphenoid sinus are an uncommon but potentially significant condition associated with thin pneumatised bone, obesity and raised intracranial pressure. Despite advances in endoscopic sinus surgery, successful repair remains problematic due to limitations in visualisation, access and management of underlying aetiological factors. Utilisation of vascularised tissue in the primary repair process of sphenoid CSF leaks is yet to be well explored in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With regard to the placement of the nasal septum mucosal flap into the posterior nostril for preparation, it was performed based on previous literature reporting the repair of spontaneous CSF leakage by taking a nasal septal pedicled skin flap under the nasal endoscope. [ 10 ] Nasal septal flap is a mucoperiosteum or mucoperichondrium that is connected to the arteria nasalis posterior septi. The nasal septum mucosal flap, used for repair of the spontaneous sphenoid cerebrospinal fluid leakage in the present study, may represent an important progress in the development of endoscopic CSF rhinorrhea repair technology.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the placement of the nasal septum mucosal flap into the posterior nostril for preparation, it was performed based on previous literature reporting the repair of spontaneous CSF leakage by taking a nasal septal pedicled skin flap under the nasal endoscope. [ 10 ] Nasal septal flap is a mucoperiosteum or mucoperichondrium that is connected to the arteria nasalis posterior septi. The nasal septum mucosal flap, used for repair of the spontaneous sphenoid cerebrospinal fluid leakage in the present study, may represent an important progress in the development of endoscopic CSF rhinorrhea repair technology.…”
Section: Discussionmentioning
confidence: 99%
“…There were no failures after primary surgery with a mean follow-up time of 14.9 months. And finally, Gunaratne and Singh 33 reported a case series of 3 patients, without LD placement, who underwent sCSF leak repair with DuraGen (Integra, Plainsboro, NJ), septal cartilage or middle turbinate bone, layered with unilateral or bilateral NSF. No patients had recurrence with a mean follow-up period of 30 months.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][21][22][23]34,35 Recent evidence-based algorithms have established NSFs as the primary workhorse for larger defects and high-flow leaks. 17,[29][30][31][32][33][34] One review showed an overall success rate of 94% for all CSF leaks while free grafts provided an 82% success rate. 34 In addition, fascia lata, as opposed to temporalis fascia, offers a very durable, bountifully available material with minimal harvest morbidity that can be harvested by a second team simultaneously.…”
Section: Scsf Leak Repair Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without intervention, the risk of developing meningitis is estimated to be 10% annually and 40% in the long term [10]. Surgical intervention remains the panacea for managing iatrogenic CSF leakages [11].…”
Section: Discussionmentioning
confidence: 99%